The Cause And Effect Of Commercial Flight On-Time Performance (Case Study : Citilink). (July 2020) - Ratnasari, Devi; Amanda, Anggi Nurul; Darmawan, Farhan; Warsito, Tito; Amonalisa, Siska
Abstract: The needs of the air transportation is increasing day by day. In order to meet the demand, airline industries made full service, medium service and low cost carrier airline concepts. However, airline concepts might have some risk factors, notably the safety factor. Not only safety factor but The time factor is also a crucial factor in airline. Sometimes airline needs to do schedule changes due to some reasons. But, in fact the airline sometimes has to delay the schedule, and will affect the on-time performance (OTP). This research is aimed to find out the cause and effect of OTP in citilink airline used exploratory descriptive research with the cause and effect diagram method. The identify categories of causes used 5M, particularly regarding Manpower, Method, Mother Nature, Machine and Management. Researchers' data collection methods are observation, interviews, and documentation, using three phases of data analysis, namely data collection, data classification, and drawing of conclusions.